Testosterone Reduces Fear and Causes Drastic Hypomethylation of Arginine Vasopressin Promoter in Medial Extended Amygdala of Male Mice - Tong, Wen Han; Abdulai-Saiku, Samira; Vyas, Ajai (Frontiers in Behavioral Neuroscience, 2019)
Testosterone reduces anxiety-like behaviors in rodents and increases exploration of anxiogenic parts of the environment. Effects of testosterone on innate defensive behaviors remain understudied. Here, we demonstrate that exogenous testosterone reduces aversion to cat odor in male mice. This is reflected as increased exploration of area containing cat urine when castrated male mice are supplied with exogenous testosterone. We also report that exogenous testosterone leads to DNA hypomethylation of arginine vasopressin (AVP) promoter in posterodorsal medial amygdala (MePD) and medial bed nucleus of stria terminalis (BNST). Our observations suggest that testosterone acting on AVP system within extended medial amygdala might regulate defensive behaviors in mice.